2017
DOI: 10.1093/ejo/cjw091
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of piezotome-corticision assisted orthodontics in alleviating mandibular anterior crowding—a randomized clinical trial

Abstract: None.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
44
2
7

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(57 citation statements)
references
References 14 publications
4
44
2
7
Order By: Relevance
“…Quelles sont les conclusions de votre récent essai clinique randomisé [77], consacré à l'utilisation d'incisions corticales piézoélectriques pour accélérer le traitement de l'encombrement antérieur mandibulaire ? Que pensez-vous des allégations d'auteurs [85] qui écrivent pouvoir ainsi diviser par trois ou quatre la durée globale d'un traitement orthodontique ?…”
Section: Interventions Chirurgicales Paunclassified
“…Quelles sont les conclusions de votre récent essai clinique randomisé [77], consacré à l'utilisation d'incisions corticales piézoélectriques pour accélérer le traitement de l'encombrement antérieur mandibulaire ? Que pensez-vous des allégations d'auteurs [85] qui écrivent pouvoir ainsi diviser par trois ou quatre la durée globale d'un traitement orthodontique ?…”
Section: Interventions Chirurgicales Paunclassified
“…5 Many methods to accelerate tooth movement have been reported in the literature to shorten treatment duration and make orthodontic treatment more acceptable to adults. 5,6 Techniques to accelerate tooth movement can be divided into surgical and nonsurgical. All surgical-orthodontic techniques are based on a biological mechanism called the regional acceleratory phenomenon (RAP) first reported by Frost.…”
Section: Introductionmentioning
confidence: 99%
“…6,11,12 Aksakalli et al 11 concluded that piezocision produced a higher rate of canine retraction and decreased the overall duration of the treatment. Uribe et al 6 reported that anterior tooth alignment was enhanced 1.6 times in the first 4 to 5 weeks after piezocision but resulted in no significant reduction of overall treatment duration. Charavet et al 12 reported that the acceleratory effect of piezocision decreased with time.…”
Section: Introductionmentioning
confidence: 99%
“…Despite being considered minimally invasive, this technique allows the addition of bone or soft tissue grafts to correct gingival recessions or bone deficiencies (15,16). The number of studies investigating piezocision effects in OTM has increased in recent years (14)(15)(16)(17)(18)(19)(20). However, there is no consensus in the existing clinical studies about its actual effectiveness, as well as in regard to the occurrence of adverse effects.…”
Section: Introductionmentioning
confidence: 99%